2011
DOI: 10.1097/jto.0b013e318219ab87
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib Accumulation in Brain Metastases from Non-small Cell Lung Cancer: Visualization by Positron Emission Tomography in a Patient Harboring a Mutation in the Epidermal Growth Factor Receptor

Abstract: Our data demonstrated that erlotinib accumulated in brain metastases in a NSCLC patient who responded to the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 14 publications
2
75
0
2
Order By: Relevance
“…However, when brain parenchymal metastases grow to >1-2 mm in diameter, the structure and function of the blood-brain barrier is disrupted, allowing drugs to enter the brain parenchyma (14). Weber et al (15) used the 11 C-marked erlotinib as a tracer with PET/CT to monitor a patient with brain metastasis from non-small-cell lung cancer. The results revealed that a high concentration of 11 C-marked erlotinib was detected in the patient's cerebellar metastasis, whereas no 11 C-marked erlotinib was detected in normal brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, when brain parenchymal metastases grow to >1-2 mm in diameter, the structure and function of the blood-brain barrier is disrupted, allowing drugs to enter the brain parenchyma (14). Weber et al (15) used the 11 C-marked erlotinib as a tracer with PET/CT to monitor a patient with brain metastasis from non-small-cell lung cancer. The results revealed that a high concentration of 11 C-marked erlotinib was detected in the patient's cerebellar metastasis, whereas no 11 C-marked erlotinib was detected in normal brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…11 C]-erlotinib has shown effective erlotinib distribution to CNS metastases but not normal brain (31). The failure of some patients to benefit from erlotinib may be explained by the expression of efflux proteins both in the BBB and in the tumor cell membrane.…”
Section: Systemic Therapy Including Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The gefitinib CSF exposure was 2.4% that of plasma, similar to previous reports (35). The CSF levels in such studies are likely to underestimate drug exposure within the tumor in the context of a disrupted BBB (31).…”
Section: Systemic Therapy Including Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…12 The clinical use of EGFR inhibitors with concurrent radiation therapy is currently being investigated in several trials, including the Radiation Therapy Oncology Group 0617 (RTOG 0617) trial. Because the small-molecule EGFR inhibitor erlotinib has shown some evidence of blood-brain barrier penetration, 15,16 we hypothesized that EGFR inhibition could be combined with WBRT to enhance the therapeutic ratio by selectively targeting the cancer cells within the brain, thereby extending survival without increasing the neurotoxicity associated with WBRT. We tested this hypothesis in NCT00871923 [Tarceva With Whole Brain Radiation Therapy-Brain Mets From Non-Small Cell Lung Cancer], a phase II clinical trial of erlotinib and concurrent WBRT for patients with brain metastases from NSCLC.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%